IMPLEMENTASI PENDEKATAN OPEN ENDED BERBANTUAN GEOGEBRA CLASSROOM UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA - Br Saragih, Apulina; Anwar; M. Zaki (Universitas Samudra, 2023)
The ability to think creatively mathematically is very important for students to face various educational challenges which are of course different, but in reality students' ability to think creatively mathematically is still relatively low. This study aims to determine the existence of an increase in students' mathematical creative thinking skills through the implementation of an open ended learning approach with the help of the geogebra classroom at SMA Negeri 2 Langsa. This study used a quantitative method with the research design used, namely the One group pre-test and post-test design. The population in this study were all students of class XI IPA SMA Negeri 2 Langsa, the sample in this study were students of class XI IPA 2 with a total of 27 students. The instrument used is a test of mathematical creative thinking ability. The test results were then analyzed using the Paired Samples T-Test. Based on the results of the analysis, the tcount value is 30.02 and the ttable value = 1.705, this means that H0 is rejected and H1 is accepted. So it can be concluded that there is an increase in students' mathematical creative thinking skills through the implementation of an open ended learning approach with the help of the Geogebra classroom at SMA Negeri 2 Langsa.